2020
DOI: 10.3389/fimmu.2020.598556
|View full text |Cite
|
Sign up to set email alerts
|

Anticancer Effect of Salvia plebeia and Its Active Compound by Improving T-Cell Activity via Blockade of PD-1/PD-L1 Interaction in Humanized PD-1 Mouse Model

Abstract: Immune checkpoint inhibitors, increasingly used to treat malignant tumors, are revolutionizing cancer treatment by improving the patient survival expectations. Despite the high antitumor efficacy of antibody therapeutics that bind to PD-1/PD-L1, study on small molecule-based PD-1/PD-L1 inhibitors is required to overcome the side effects of antibody therapeutics caused by their size and affinity. Herein, we investigated antitumor potential of Salvia plebeia R. Br. extract (SPE), which has been used as a traditi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
30
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 33 publications
(31 citation statements)
references
References 45 publications
1
30
0
Order By: Relevance
“…We hypothesized that SRE induces antitumor responses to blockade PD-1/PD-L1, as T cell activation by medicinal herb extracts has previously been reported ( 20 ). To confirm the cytotoxicity of SRE against murine CRC hPD-L1 MC38 cells and hPD-L1 MC38 cell-bearing hPD-1 mice-isolated splenocytes, cells were incubated with various concentrations of SRE for 72 hours.…”
Section: Resultsmentioning
confidence: 96%
See 2 more Smart Citations
“…We hypothesized that SRE induces antitumor responses to blockade PD-1/PD-L1, as T cell activation by medicinal herb extracts has previously been reported ( 20 ). To confirm the cytotoxicity of SRE against murine CRC hPD-L1 MC38 cells and hPD-L1 MC38 cell-bearing hPD-1 mice-isolated splenocytes, cells were incubated with various concentrations of SRE for 72 hours.…”
Section: Resultsmentioning
confidence: 96%
“…To elucidate the effect of SRE on TCR activation, we conducted coculture systems using human PD-1-expressing Jurkat T cells that expressed NFAT-derived luciferase reporter (hPD-1/NFAT Jurkat cells) and human PD-L1-expressing aAPC/CHO-K1 cells designed to activate cognate TCR (hPD-L1/TCR CHO-K1 cells). The cell culture model was established to evaluate the effect of PD-1/PD-L1 blockade ( 20 ). To examine the cytotoxic effects of SRE, hPD-1 effector cells and hPD-L1/TCR CHO-K1 cells were treated with the indicated concentration (0–50 μg/mL) of SRE for 24 hours.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Choi et al reported that Salvia plebeia R. Br. extract (SPE) blocked the interactions between PD-1 and PD-L1 [ 115 ]. Two flavonoids including apigenin and cosmosiin (Fig.…”
Section: Natural Product-derived Pd-1/pd-l1 Inhibitorsmentioning
confidence: 99%
“…Recently, using competitive ELISA, we showed Rhus vernicifua Stokes alone as an active inhibitor with a PD-1/PD-L1 blocking effect [ 31 ]. In addition, we previously reported the anticancer properties of several herbal medications: Sanguisorbae radix, Salvia plebeia , and RCE were each used alone as monotherapy via the inhibition of PD-1/PD-L1, and these were verified to be effective at non-toxic concentrations [ 28 , 32 , 33 ]. To confirm the clinical applicability of these herbal medications and expand their use, we sought to develop an innovative combination therapy with RCE aimed at blocking PD-1/PD-L1 binding.…”
Section: Introductionmentioning
confidence: 99%